INFIXATION AND APOPHONY IN MALAY: DESCRIPTION AND DEVELOPMENTAL STAGES - Timothy McKinnon; NFN Yanti; Peter Cole; Gabriella Hermon (Masyarakat Linguistik Indonesia, 2015)
Malay(ic) languages of Sumatra show a high level of internal diversity. Linguists are only beginning to understand the ways in which these languages differ from one another, and what this divergence tells us about the origins and development of Malay. This paper describes an important morphological phenomenon in Sumatran Malay: morphological word-shape alternations. Kerinci, a Malayic language spoken in the Bukit Barisan range in Jambi, exemplifies this phenomenon. Kerinci exhibits a morphological alternation which is realized in the final –V(C) of roots (e.g. ataʔ ‘roof’ vs. atək ‘the/its roof’) (Prentice & Usman, 1978; Steinhauer & Usman, 1978) inter alia). Previous studies have concluded that word-shape alternations of this sort are attested only in a subregion of Kerinci (cf. Usman, 1988). In this paper, we show that word-shape alternations resembling those found in Kerinci can be found sporadically throughout a large region of Sumatra, in both Minangkabau and Traditional Malay varieties. We describe these phenomena, and develop a historical account of their development. We conclude that word-shape alternations developed independently in several varieties as a result of shared prosodic properties.